INCREASING VOLUME HARDNESS OF STEEL GRINDING BALLS USING Q-n-P HEAT TREATMENT - Zurnadzhy, V. I.; Efremenko, V. G.; Dunaev, E. V.; Lekatou, A.; Kussa, R. A. (Science and Transport Progress, 2018)
Purpose. This study investigates the possibility of improving the quality of grinding steel balls with a diameter of 100 mm by using Q-n-P heat treatment. Methodology. Steel grinding balls with a diameter of 100 mm, obtained by transverse screw rolling, were used as a material. The heat treatment consisted of balls quenching in a drum-type device according to various modes and subsequent tempering. The quenching modes provided the bulk temperature of the balls in the range of 120-240 оС, which is lower than the martensitic point Ms of the steel. After quenching, the balls were immediately tempered at 170-300 °C for 2-10 hours. The treated balls were visually examined, tested for hardness and impact resistance. The hardness was measured according to the Rockwell method by scale "C", the microhardness was measured with microhardness tester "Affri" at a load of 50 g. The impact resistance of the balls was evaluated by impact of a dropped load with impact energy of 6.8 kJ. Microstructural analysis was conducted using an optical microscope "Axiovert 40-M". The amount of residual austenite was determined using an "IV-Pro Rigaku" diffractometer in copper Ka-radiation. Findings. It is shown that, as a result of treatment of 100 mm diameter balls of chromium-manganese steel according the standard mode, the cracks occur on balls surface. Using Q-n-P heat treatment allows achieving higher hardness through the cross section (within 54-57 HRC) while quenching cracks are absent on the balls. The Q-n-P-treated balls have high impact resistance under repeated impacts with energy of 6.8 kJ. Originality. For the first time the authors investigated the feasibility of using the Q-n-P heat treatment for steel grinding balls of large diameter made of steel with increased hardenability. It has been determined that Q-n-P-processing allows to significantly increase (by 10 HRC) the bulk hardness of 100 mm diameter balls, while retaining their high impact resistance in tests with a dropped load. The obtaining of such properties is pro-vided by the relaxation of quenching stresses and the formation of a two-phase martensitic-austenite structure with an increased amount (25-30 %) of retained austenite. The latter becomes possible due to the process of partitioning carbon from martensite to austenite with enrichment of the latter to 1.12 % C. Practical value. The advisability of Q-n-P-heat treatment in the production of steel grinding balls with higher bulk hardness is shown.